Expression Profile and Functional Characterization Suggesting the Involvement of Three Chemosensory Proteins in Perception of Host Plant Volatiles in Chilo suppressalis (Lepidoptera: Pyralidae). Issue 5 (27th September 2018) - Khuhro, Sajjad Ali; Yan, Qi; Liao, Hui; Zhu, Guan-Heng; Sun, Jia-Bin; Dong, Shuang-Lin
Abstract: The high sensitivity of the olfactory system is essential for feeding and oviposition in moth insects, and some chemosensory proteins (CSPs) are thought to play roles in this system by binding and carrying hydrophobic odorants across the aqueous sensillar lymph. In this study, to identify the olfactory CSPs from a repertoire of 21 CSP members in the notorious rice pest Chilo suppressalis (Walker) (Lepidoptera: Pyralidae), tissue expression patterns were firstly examined by quantitative real-time polymerase chain reaction (qPCR). It showed that CSP 2 was antennae specific and seven more CSPs ( CSP1, 3, 4, 6, 15, 16, and 17 ) were antennae biased in expression, suggesting their olfactory roles; while other CSPs were multiple-tissue expressed and non-antennae biased, suggesting other functions for these genes. To further determine the ligand binding specificity, three putative olfactory genes ( CSP1 – 3 ) were expressed in Escherichia coli cells, and binding affinity of these three recombinant CSP proteins were measured for 35 plant volatiles by the ligand binding assays. CSP1 and CSP2 exhibited high binding affinities (Ki ≤ 10.00 µM) for four (2-tridecanone, benzaldehyde, laurinaldehyde and 2-pentadecanone) and two (2-heptanol and (+)-cedrol) host plant volatiles, respectively; the three CSPs also showed moderate binding affinity (Ki = 10.01–20.00 µM) for 16 plant volatiles. Our study suggests that the three CSPs play essential roles in the perception of host plant volatiles, providing bases for the elucidation of olfactory mechanisms in this important pyralid pest.